Comparison of peribulbar anesthesia and topical anesthesia on outcome of phacoemulsification - Mehta, Rishi; Punjabi, Sharda; Bedi, Nutan; Nagar, Chandra Kant (International Journal of Research in Medical Sciences, 2017)
Background: Due to advancement in phacoemulsification techniques, there has been growing shift from peribulbar anesthesia (PA) to topical anesthesia (TA). But dilemma exists regarding the supremacy of one over the other as both types have certain advantages and disadvantages. Methods: A prospective study was conducted. Patients were divided into two groups. Group-1 underwent PA while group-2 underwent TA. Satisfaction score of patients and surgeons and incidence of complications were noted. The data was analyzed. Results: Lowest patients’ satisfaction score among group-1 vs. group-2 was 160 (87.9%) vs.82 (45.81%). Highest surgeons satisfaction score among group-1 and group-2 was 74(40.65%) vs. 2(1.1%). Intraoperative complications among the group-1 and group-2 were 35 (19.2%) vs. 86(48.0%). Conclusions: While TA provides initial painless phase of surgical procedure, PA results in lesser intraoperative complications resulting in better visual outcome.